Profile of Relugolix in the Management of Advanced Hormone-Sensitive Prostate Cancer: Design, Development, and Place in Therapy - Tatenuma T; Miyamoto H (Drug Design, Development and Therapy, 2023)
Tomoyuki Tatenuma,1,2 Hiroshi Miyamoto1,3 1Department of Pathology & Laboratory Medicine, University of Rochester Medical Center, Rochester, NY, USA; 2Department of Urology, Yokohama City University Graduate School of Medicine, Yokohama, Japan; 3Department of Urology, University of Rochester Medical Center, Rochester, NY, USACorrespondence: Hiroshi Miyamoto, Department of Pathology & Laboratory Medicine, University of Rochester Medical Center, 601 Elmwood Avenue, Box 626, Rochester, NY, 14642, USA, Tel +1 585 275 8748, Fax +1 585 273 3637, Email hiroshi_miyamoto@urmc.rochester.eduAbstract: Androgen deprivation therapy, primarily via a gonadotropin-releasing hormone receptor agonist or antagonist together with or without an androgen receptor antagonist, remains the mainstay of medical treatment for advanced prostate cancer. Meanwhile, relugolix has been developed as the first orally active, non-peptide, selective antagonist for the gonadotropin-releasing hormone receptor. Previous randomized studies involving patients with prostate cancer have demonstrated comparable efficacy in androgen suppression between relugolix vs other gonadotropin-releasing hormone antagonists or agonists. This review summarizes available data on the design and development of relugolix and its therapeutic application, and discusses if relugolix represents a promising oral alternative to injectable androgen deprivation therapy. Based on current published evidence, further investigation is likely required to determine the actual clinical benefits of relugolix therapy against prostate cancer.Keywords: androgen deprivation therapy, gonadotropin-releasing hormone antagonist, prostate cancer, relugolix